Chapter 2. A multi-criteria strategy for assessing the quality of frozen raw cherry fruits - Ivanova, Iryna; Іванова, Ірина Євгенівна; Serdyuk, Maryna; Сердюк, Марина Єгорівна; Tymoshchuk, Tetiana; Тимощук, Тетяна Миколаївна; Drobitko, Antonina; Pyurko, Olga; Mulienok, Yana (Scientific Route Tallinn Estonia, 2025)
EN: The optimization of the food chains, in particular the storage and processing of raw materials into final products, is becoming a particularly difficult task for the regions which face humanitarian crises, protracted political conflicts and natural disasters. Cherries are one of the most popular fruits in the confectionary industry used. Freezing is one of the most effective methods of long-term preservation of cherries. At the same time, frozen raw materials, like any other product, can undergo changes that negatively affect the quality of the final product. This may include deterioration of taste characteristics, loss of vitamins, and risk of developing microbiological processes in case of the violation of storage or transportation conditions. In this context, the implementation of comprehensive assessment of the cherry fruits quality becomes especially relevant. Therefore, systematic monitoring of physical, biochemical and sensory parameters is necessary to obtain high-quality frozen raw materials. A method of multi-criteria evaluation of frozen fruit was proposed. The objective functions were calculated and a ranking series of the suitability of the frozen fruits for the production of candied fruit was formed. By using a multi-criteria optimization method, the most suitable cherry cultivars for freezing were determined. A scientifically based complex of quality parameters of functional technological indicators of frozen fruit is presented. The selection of the optimal cultivar of fruit raw materials with high quality indicators and minimal losses was carried out by means of a comparative evaluation of the cultivars according to their properties using a multi-criteria method based on a geometric convolution of criteria. Chemical, physical and organoleptic criteria of frozen semi-finished products may change depending on the varietal characteristics of cherries. Therefore, choosing the optimal cultivar requires a comprehensive approach. The use of a multi-criteria optimization method made it possible to establish relationships between the quality characteristics of the fruits and their permissible values. This made it possible to determine the fruit of Griot Melitopol cultivar as the best frozen raw material according to functional, technological and sensory indicators. This can further be used to improve criteria for evaluating the quality of frozen fruit pulp within a zero-waste fruit supply chain, ensuring efficiency and sustainable use of resources for all stakeholders. /// UA: Оптимізація продовольчих ланцюгів, зокрема зберігання та переробки сировини в кінцеву продукцію, стає особливо складним завданням для регіонів, які стикаються з гуманітарними кризами, затяжними політичними конфліктами та стихійними лихами. Вишня - один з найпопулярніших фруктів в кондитерській промисловості, використовуваних в кондитерській промисловості. Заморожування є одним з найбільш ефективних методів тривалого збереження вишні. При цьому заморожена сировина, як і будь-який інший продукт, може зазнавати змін, які негативно позначаються на якості кінцевого продукту. Сюди можна віднести погіршення смакових характеристик, втрату вітамінів, ризик розвитку мікробіологічних процесів при порушенні умов зберігання або транспортування. У цьому контексті особливо актуальним набуває здійснення комплексної оцінки якості плодів черешні. Тому для отримання високоякісної замороженої сировини необхідний систематичний моніторинг фізичних, біохімічних і сенсорних показників. Запропоновано метод багатокритеріальної оцінки заморожених фруктів. Розраховано цільові функції та сформовано ранжовий ряд придатності заморожених плодів для виробництва цукатів. За допомогою багатокритеріального методу оптимізації було визначено найбільш підходящі сорти вишні для заморожування. Представлено науково обґрунтований комплекс якісних параметрів функціональних технологічних показників заморожених фруктів. Підбір оптимального сорту плодової сировини з високими якісними показниками та мінімальними втратами здійснювався шляхом порівняльної оцінки сортів за їх властивостями за допомогою багатокритеріального методу, заснованого на геометричній згортці критеріїв. Хімічні, фізичні та органолептичні критерії заморожених напівфабрикатів можуть змінюватися в залежності від сортових особливостей вишні. Тому вибір оптимального сорту вимагає комплексного підходу. Використання багатокритеріального методу оптимізації дозволило встановити взаємозв'язки між якісними характеристиками плодів і їх допустимими значеннями. Це дозволило визначити плоди сорту Гріот Мелітополь як найкращу заморожену сировину за функціональними, технологічними та сенсорними показниками. Це також може бути використано для вдосконалення критеріїв оцінки якості замороженої фруктової м'якоті в рамках безвідходного ланцюга поставок фруктів, забезпечуючи ефективність і стале використання ресурсів для всіх зацікавлених сторін.
Розділ 2. Багатокритеріальна стратегія оцінки якості заморожених сирих плодів вишні
Keywords: fruit; amount of juice loss; sensory analysis; biochemical indicators; freezing; storage; geometric convolution criteria; фрукти; величина втрати соку; сенсорний аналіз; біохімічні показники; заморожування; зберігання; геометричні критерії згортки